2020
DOI: 10.21037/jgo-20-208
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the prognosis for chromobox family in gastric cancer

Abstract: Background: Chromobox (CBX) family proteins are a class of transcriptional repressors involved in epigenetic regulation and developmental processes of various tumors, including gastric cancer. However, the function and prognosis of different CBXs in gastric cancer remain unknown. Methods: This study addresses this issue by synthesizing several mainstream databases (Oncomine, GEPIA2, cBioportal, and Kaplan-Meier plotter, among others) that currently contain many tumor samples and provide very reliable analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…In previous studies, overexpression of CBX1 has been found in many cancers such as hepatocellular carcinoma ( 33 , 34 ), gastric cancer ( 35 , 36 ), colorectal cancer ( 37 ), and pituitary cancer ( 38 ). In HCC, CBX1 functions as an oncogene by interacting with the transcription factor HMGA2 to activate the Wnt/β-catenin signaling pathway ( 33 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In previous studies, overexpression of CBX1 has been found in many cancers such as hepatocellular carcinoma ( 33 , 34 ), gastric cancer ( 35 , 36 ), colorectal cancer ( 37 ), and pituitary cancer ( 38 ). In HCC, CBX1 functions as an oncogene by interacting with the transcription factor HMGA2 to activate the Wnt/β-catenin signaling pathway ( 33 ).…”
Section: Discussionmentioning
confidence: 95%
“…Overexpression of CBX3 has also been observed in many malignancies such as lung cancer ( 43 , 44 ), gastric cancer ( 36 , 45 ), and tongue squamous cell carcinoma ( 46 , 47 ). High CBX3 targets CDKN1A to promote the proliferation of U87 cells and predicts poor recurrence-free survival and OS in glioma patients ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Kaplan–Meier plotter showed that high CBX7 mRNA expression was associated with poor OS. One explanation for this finding is that although CBX7 mRNA expression is low in cancer tissues, CBX7 protein expression is significantly elevated in tumor tissues 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CBX8 plays a signi cant role in lymphoma, breast carcinoma, esophageal squamous cell carcinoma, esophageal cancer, and other human cancers [41]. Studies carried out by Yuan et al showed that upregulated CBX8 was associated with the progression of the stages in muscle-invasive bladder cancer tissues by repressing the p53 pathway [42].…”
Section: Discussionmentioning
confidence: 99%